Users’ satisfaction with usability of Putrajaya parks in relation to post-occupancy evaluation - Talib, Nor' Aini (2017)
Public parks are designed for people to experience nature; hence, these places need to provide various facilities for human activities. As public parks are important to people of all levels in the society, conducting research on Post Occupancy Evaluation (POE) of public parks in Putrajaya is viewed as the first step towards evaluating the success of public parks in Malaysia. Despite the huge amount of money spent in developing and maintaining these parks and gardens, there seems to be a lack of research on POE of the parks and gardens in the country. Therefore, this study was carried out to analyse the status of three public parks in Putrajaya by observing the activities in each park and mapping the activity patterns onto an Activity Map. Observations and surveys were conducted involving visitors to these three parks: Botanical Park (BP), Pancarona Park (PP) and Putra Perdana Park (PPP). The POE was carried out based on the criteria set for successful public spaces and important factors in analysing the performance of a park such as design criteria, operations and maintenance work. Questionnaires distributed yielded a total of 447 responses obtained from park visitors at BP (220), PPP (152) and PP (71). The questionnaire contained closed and open-ended items and was divided into the following sections: demographics of visitors, information on park usage, user needs, user satisfaction, park setting arrangement, operations and maintenance. The results revealed that the visitors were satisfied with the accessibility, park safety, design pattern and facilities provided in each park. The results also indicated that as far as safety is concerned, visitors felt comfortable to use the parks as these parks were well-maintained. Observation also showed that visitors used the parks according to their activities. PPP was used mostly for jogging while BP was used for cycling, and PP was used for sports activities. The activity mapping done showed the details of each activity and the areas usually occupied by the visitors. However, not all of the spaces or areas in each park were utilised by the visitors. Activity mapping showed that most of the activities took place only in certain concentrated areas. There were a total of 13 parks in Putrajaya at the time the study was conducted; however, the three case studies were sufficient to show that visitors used the parks only for recreational purposes. The findings of this study will be useful for those involved in the development of public parks such as landscape architects, maintenance managers and planners, regardless of whether they are directly involved or not. It is hoped that the findings of this research have managed to convince relevant parties on the importance of carrying out the POE in the future. The POE provides guidance on how to upgrade existing parks in Malaysia so that the number of visitors will increase in the future.